Effects of V-1 and angiotensin receptor subtypes of the paraventricular nucleus on the water intake induced by vasopressin injected into the lateral septal area - Camargo, LAD; Saad, W. A.; Cerri, Paulo Sérgio [UNESP] (Elsevier B.V., 2003)
In this study, we investigated the influence of d(CH2)(5)-Tyr (Me)-AVP (AAVP) an antagonist of V-1 receptors of arginine(8)-vasopressin (AVP) and the effects of losartan and CGP42112A (selective ligands of the AT, and AT, angiotensin receptors, respectively) injections into the paraventricular nucleus (PVN) on the thirst effects of AVP stimulation of the lateral septal area (LSA). AVP injection into the LSA increased the water intake in a dose-dependent manner. AAVP injected into the PVN produced a dose-dependent reduction of the drinking responses elicited by LSA administration of AVP. Both the AT(1) and AT(2) ligands administered into the PVN elicited a concentration-dependent inhibition in the water intake induced by AVP injected into the LSA, but losartan was more effective than CGP42112A the increase in the AVP response. These results indicate that LSA dipsogenic effects induced by AVP are mediated primarily by PVN AT(1) receptors. However, doses of losartan were more effective when combined with CGP42112A than when given alone, suggesting that the thirst induced by AVP injections into LSA may involve activation of multiple angiotensin II (ANG II) receptor subtypes. These results also suggests that facilitatory effects of AVP on water intake into the LSA are mediated through the activation of V-receptors and that the inhibitory effect requires V-receptors. Based on the present findings, we suggest that the administration of AVP into the LSA may play a role in the PVN control of water control. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: vasopressin; antagonist V-1; angiotensin receptor subtypes; water intake; septal lateral area; paraventricular nucleus